Assessment of the properties of diamond-like carbon coatings (DLC) used in the lime industry - K. Milewski; K. Piotrowska; M. Madej (Metalurgija, 2024)
The aim of the study was to analyze the properties of diamond-like carbon coatings - DLC in machines operating in the lime industry. DLC coatings were deposited by the Plasma-Enhanced Chemical Vapor Deposition PECVD method on 100Cr6 steel samples. Characterization of the geometric structure of samples was carried out on an optical profilometer. The friction junctions were tested in harsh conditions, i.e., corrosive environment and high temperature. The tribological tests were performed using a sliding ball-on-disc tribological tester. The static contact angle for selected lubricants was measured using an optical tensiometer. The summary presents the possibilities of using diamond-like coatings in selected friction junctions in the lime industry.